Extrusion of poly(vinylidene fluoride) filaments : effect of the processing conditions and conductive inner core on the electroactive phase content and mechanical properties - Ferreira, A. (2011)
The phase transformation from the α- to the electroactive β-phase of poly(vinylidene fluoride) (PVDF) extruded filaments submitted to different stretching conditions was investigated. Sample filaments of α-PVDF thermoplastic were extruded and stretched uniaxially at different temperatures (80 ºC to 120 ºC) and stretch ratios (1 to 6). The stretched samples were studied and characterised by x-ray diffraction and quasi-static mechanical experiments. High β-phase contents (~ 80%) are achieved using a stretch ratio of 5 independently of the stretching temperature, between 80 ºC and 120 ºC. Subsequently, in order to obtain filament geometries and material configurations suitable for application, a two layer filament with coaxial layers was produced by coextrusion. The inner layer consisted of a commercially available grade of a conductive thermoplastic with a polypropylene (PP) matrix. For the outer layer the same grade of PVDF was employed. The double-layer filament was also stretched under the same conditions of the PVDF filaments and the results obtained shows that the inner layer material, acting as an electrode, does not have any influence in the PVDF crystallization process: PVDF crystallizes in the α-phase for stretch ratios of 1 and the α to β-phase transformation occurs for higher stretch ratios.